Improving performance tracking, knowledge generation, and learning for effective result-based management: Sub Saharan Africa monitoring, evaluation & learning (ME&L) strategy - Mulongo, G.; Sindi, K.; Okello, J.J.; Wanjohi, L.; Mudege, Netsayi N.; Quinn, S. (International Potato Center, 2015)
To reinforce the culture of good, efficient and user-friendly knowledge management and communication in CIP-SSA, this strategy will institutionalize and provide resources necessary to support and nurture the environment that will stimulate knowledge generation, sharing, communication, and management in order to foster organizational learning.